Capital Structure Analysis in Healthcare Issuers in the DES Category for 2017-2019 - Riyandi, Taufik; Riyanto, Setyo (Interdisciplinary Social Studies, 2022)
There is an increasing trend of sustainable healthy lifestyles and strong industrial potential amid a pandemic. To seize this opportunity, health companies need to increase their production capacity, and ultimately the company needs capital for its operations. Thus, it is necessary to analyze the optimal capital structure to reduce so that the company can maximize its value of the company. This study aims to analyze the company's cost of capital and analyze the optimal capital structure of the company in the pharmaceutical industry on the Sharia Stock List (DES), which is listed on the Indonesia Stock Exchange (IDX) for 2017-2019 period. The analysis was carried out by calculating the WACC, then comparing the average industrial WACC with the average value of the pharmaceutical industry companies so that they could analyze the capital structure optimally for each issuer. Calculation using Microsoft Excel 2016. The average industrial issuer was dominated by the capital structure originating from equity. In addition, the calculation of the industrial average WACC and the average value of industrial companies is 8.00% and Rp. 374,302,- (in Millions of Rupiah) where KLBF is a pharmaceutical issuer that has an optimal capital structure, namely WACC below the industry average and company value above the industry average. There is company management that is more careful and careful in determining the company's capital structure, even for working capital and or for investment, so that an optimal combination is achieved and can increase company value and reduce company risk.